Masterful women : slaveholding widows from the American Revolution through the Civil War - Wood, Kirsten E. (Gender & American culture., 2004)
Many early-19th-century slaveholders considered themselves "masters" not only over slaves, but also over the institutions of marriage and family. This privilege was generally reserved for white males. But as many as one in ten slaveholders was a widow, and as this book demonstrates, slaveholding widows developed their own version of mastery.